Report on Evaluation Study of the Growth Centres Schemes - Planning Commission (Planning Commission Government of India, 2005)
The Growth Centres Scheme, launched by the Government of India in 1991, aimed to promote industrialization in backward and remote regions to reduce regional disparities. An evaluation conducted by the Programme Evaluation Organisation (PEO) in 2005 assessed the scheme’s effectiveness in achieving its objectives. The study revealed limited financial utilization, with only 32% of the approved funds released, and significant gaps in land acquisition and plot development. Of the 840 industrial units established, nearly 46% were non-viable or closed, highlighting weak industrial uptake. Key challenges included inadequate infrastructure, delayed land acquisition, low entrepreneurial interest, and insufficient monitoring and coordination. The evaluation recommended halting further central funding, prioritizing infrastructure development, implementing fixed review mechanisms, offering tailored incentives to entrepreneurs, and focusing resources on the most industrially backward regions. Overall, the findings emphasize the need for a localized, infrastructure-driven, and strategically coordinated approach to foster sustainable industrial growth and reduce regional disparities in India.
Programme Evaluation Organisation Planning Commission Government of India New Delhi-110001 October, 2005
Keywords: Growth Centres Scheme; Industrialization; Regional Inequalities; Infrastructure Development; Land Acquisition; Industrial Units; Employment Generation; Monitoring And Coordination; Entrepreneurial Attraction; Backward Areas; Financial Performance; Strategic Recommendations